Validated LC--MS/MS method for determination of YH-8, a novel PKnB inhibitor, in rat plasma and its application to pharmacokinetic study - Qianqian Zhai; Jing Pang; Guoqing Li; Congran Li; Xinyi Yang; Liyan Yu; Yucheng Wang; Jian Li; Xuefu You (Elsevier, 2015)
(E)-Methyl-4-aryl-4-oxabut-2-enoate (YH-8) is a novel PKnB protein kinase inhibitor with good anti-tuberculosis activity. To evaluate its pharmacokinetics in rats, a sensitive and selective high performance liquid chromatography-tandem mass spectrometric (LC--MS/MS) method has been developed and validated for the quantification of YH-8 in rat plasma for the first time. Samples were pre-treated using a liquid--liquid extraction with ethyl acetate and the chromatographic separation was performed on a C18 column by gradient elution with methanol--water as the mobile phase. YH-8 was detected using a tandem mass spectrometer in positive selected reaction monitoring (SRM) mode. Method validation revealed good linearity over the range of 1-500 ng/mL for YH-8 with a lower limit of quantification (LLOQ) of 1 ng/mL. Intra- and inter-day precision of YH-8 assay in rat plasma samples were 2.0%-6.8%, with accuracy of the method being 100.69%-106.18%. Stability test showed that when spiked into rat plasma, YH-8 was stable for 12 h at room temperature, for up to 15 days at −70 °C, and after three freeze-thaw cycles. Extracted samples were found to be stable over 12 h in an auto-sampler. The method was successfully applied to the pharmacokinetic study of YH-8 in rats after oral administration at 100 mg/kg and 200 mg/kg.